Advertising on TV: Under- or overprovision? - Hans Jarle Kind; Tore Nilssen; Lars Sørgard (University of Oslo, Department of Economics, 2005)
We consider a model where TV channels transmit advertising, and viewers dislike such commercials. We find that the less differentiated the TV channels' programs are, the lower is the amount of advertising in equilibrium. Relative to the social optimum, there is underprovision of advertising if TV channels are sufficiently close substitutes. In such a situation, a merger between TV channels may lead to more advertising and thus improve welfare. A publicly owned TV channel can partly correct market distortions, in some cases by having a larger amount of advertising than a private TV channel. It may actually have advertising even in cases where it is wasteful per se.
Keywords: L82; M37; 330; Television industry; Advertising; Public policy; Mixed oligopoly; Fernsehwerbung; Fernsehanstalt; Medienverhalten; Theorie